Neuroprotective mechanisms of selenium against arsenic-induced behavioral impairments in rats (2020)
Environmental pollution due to arsenic is associated with several adverse health effects including neurotoxicity in animals and humans. Selenium is a nutritionally essential trace metalloid well documented to elicit com- pelling pharmacological activities in vitro and in vivo. Report on the influence of selenium on arsenic-mediated behavioral derangement is lacking in literature. Hence, to fill this knowledge gap, rats were either exposed to arsenic per se in drinking water at 60 pg AsO2Na/L or co-administered with inorganic selenium at 0.25 mg/kg or organic selenium diphenyl diselenide (DPDS) at 2.5 mg/kg body weight for 45 successive days. Neurobehavioural data from rats in a new environment using video-tracking software evinced that inorganic and organic forms of selenium significantly (p < 0.05) abrogated arsenic-induced motor and locomotor in- sufficiencies such as increased negative geotaxis and fecal pellets numbers as well as the diminution in grip strength, body rotation, maximum speed, absolute turn angle and total distance travelled. The augmentation in the behavioral activities in rats co-administered with arsenic and both forms of selenium was substantiated using track and occupancy plots analyses. Selenium mitigated arsenic-induced decreases in glutathione level and acetylcholinesterase activity as well as the increase in oxidative stress and reactive oxygen and nitrogen species. Moreover, selenium diminished inflammatory parameters (myeloperoxidase activity, nitric oxide, tumour ne- crosis factor alpha and interleukin-1 beta levels), caspase-3 activity and ameliorated histological lesions in the cerebellum, cerebrum and liver of the rats. Collectively, selenium abated arsenic-induced behavioral derange- ments via anti-inflammation, antioxidant and anti-apoptotic mechanisms in rats.